Excellence Service Library USU Kebencanaan Akibat Pandemi - Juli Purnawati (Al-Ma'mun: Jurnal Kajian Kepustakawanan dan Informasi, 2022)
In accordance with the motto of the USU Library "Library is the Heart of the University", of course the academic community within USU really needs library services. As a result of the covid19 pandemic, which was faced by USU to continue to provide the best services that could be utilized by the academic community of the University of North Sumatra. This paper aims to explain and find out the innovations made through the USU library's excellent service: disaster due to pandemic. Excellence services available are: 1). Turniti test service, 2). University library book ordering service, 3). Branch library book ordering service, 4). Short loan collection book ordering service (KPS), 5). Student Final Project Services, 6). Service for ordering e-journal articles and e-books, 7). SKBP (library free certificate). The method used is a literature study. The data sources for this paper are the USU Library's web and social media. The results of this study are 1). Access: convenience and facilities, 2). Content: number of types, and organization, 3). Search facility: search system, and display of results.